2022
DOI: 10.3390/jcm12010137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Results of TTF-1 Immunostaining on Efficacy of Platinum-Doublet Chemotherapy in Japanese Patients with Nonsquamous Non-Small-Cell Lung Cancer

Abstract: Background: Pemetrexed is a key drug in chemotherapy for nonsquamous non-small-cell lung cancer (nonsq NSCLC). Several studies have reported thyroid transcription factor-1 (TTF-1) as a biomarker of the efficacy in chemotherapy regimens, including pemetrexed in non-Asian people. Objective: We aimed to examine the impact of the results of the TTF-1 immunostaining of tumor cells on the therapeutic effect of chemotherapy in Japanese patients with nonsq NSCLC. Methods: We examined the results of TTF-1 immunostainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Previous reports have suggested that pemetrexed is less effective in patients with smoking history and TTF-1 negativity. 20 , 21 , 22 , 23 Thus, considering the possibility of similarities between TTF-1–negative and focally TTF-1–positive tumors, which have been seemed to be less effective toward pemetrexed, the results of our study indicated that survival response to chemoimmunotherapy including pemetrexed was significantly better in patients with diffusely TTF-1–positive tumors.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Previous reports have suggested that pemetrexed is less effective in patients with smoking history and TTF-1 negativity. 20 , 21 , 22 , 23 Thus, considering the possibility of similarities between TTF-1–negative and focally TTF-1–positive tumors, which have been seemed to be less effective toward pemetrexed, the results of our study indicated that survival response to chemoimmunotherapy including pemetrexed was significantly better in patients with diffusely TTF-1–positive tumors.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies exploring TTF-1 expression status as a treatment response marker reported that the PFS and OS were significantly better in patients with TTF-1–positive tumors than in those with TTF-1–negative tumors. 13 , 14 , 18 , 19 , 20 , 32 , 33 , 34 Low thymidylate synthase, which is the main target of pemetrexed, was also associated with significantly better clinical response in patients with advanced nonsquamous NSCLC receiving pemetrexed-based chemotherapy. 18 , 35 Nevertheless, some patients with TTF-1–positive tumors exhibited minimal response to chemoimmunotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Another study showed that the PFS and OS of TTF-1-negative patients improved after administration of PEM-free platinum regimens, whereas OS was the same regardless of the regimen in TTF-1-positive patients [18]. Two studies from Asian countries reported that TTF-1 status is a prognostic factor rather than a predictive factor of the response to platinum-based chemotherapy including PEM [24,25]. However, those studies included patients with EGFR/ALK mutations.…”
Section: Discussionmentioning
confidence: 99%